(untitled) (CIPEEX, 2025)
Global population aging brings significant challenges to public health, especially regarding the increased risk of falls among the elderly, which can be exacerbated by conditions such as hypertension. These factors are associated with health problems that can lead to serious accidents, loss of autonomy, and a reduction in the quality of life for the elderly. The objective of this study was to compare the risk of falls, lower limb muscle strength, and postural balance in elderly individuals with and without hypertension. An analytical cross-sectional observational study was conducted with 106 elderly individuals enrolled at UniAPI, of which 10 met the inclusion criteria. Sociodemographic information was collected and assessments of fall risk, cognitive level, and muscle strength were conducted. The results showed that hypertensive elderly individuals performed significantly worse on the Sit-to-Stand Test (SST) compared to healthy individuals, reflecting reduced functional capacity. However, no significant differences were found in postural balance between elderly individuals with and without hypertension, as indicated by the values of center of gravity displacement and velocity. These findings indicate that when hypertension is controlled, there is no impact on postural balance control. The absence of significant differences reinforces the need for intervention strategies to improve the mobility and muscle strength of patients with cardiovascular conditions, aiming at fall prevention and the improvement of the quality of life of the elderly.